Implementation of Performance Assessment in Guitar Instruction within Music Education - Mochammad Wira Adi Pratama; Kidung Sukma Asmarani (CV. Edujavare Publishing, 2026)
Music education requires assessment practices that can authentically measure students' practical performance skills. This study aims to describe the implementation of performance assessment in guitar instruction for Grade X Accounting and Financial Institution (AKL 1) students at SMK Negeri 1 Brebes. The study employed a qualitative descriptive approach. Data were collected through classroom observations, semi-structured interviews, and document analysis, including the Learning Objectives Flow (ATP), Learning Objectives Achievement Criteria (KKTP), teaching modules, assessment rubrics, students' achievement records, and instructional documentation. Data were analyzed through data reduction, data display, and conclusion drawing, while data trustworthiness was established through source and methodological triangulation. The findings indicate that the implementation of performance assessment encompasses four interconnected stages: assessment planning, instrument development, assessment implementation, and utilization of assessment results. The assessment employed an analytic rubric evaluating students' guitar playing techniques, chord accuracy, tempo and rhythm, as well as musical expression and stage performance. Performance assessment was conducted through both individual and group practical performances, and the results were utilized to support remedial instruction, enrichment activities, and the determination of final grades. The findings further demonstrate that performance assessment provides an authentic representation of students' progress in developing guitar performance skills.